Comparative evaluation of three buffalo populations using microsatellite markers - Vijh, R K; Mishra, Bina; Arora, Reena; chaudhry, Preeti; Sharma, Uma; Tantia, M S (The Indian Journal of Animal Sciences, 2005)
Data generated on 24 microsatellite loci from 3 buffalo populations viz. Bhadawari, Tarai and Kerala buffaloes was subjected to analysis for estimation of genetic distances. The genetic distances calculated were Nei’s minimum, Nei’s standard, Latter’s Fst, Reynolds’ distances (IAM). The genetic distances based on SMM were also estimated. These were average squared distance (ASD), delta mu square [()’], Shrivers’ Dsw and similarity index (D,). The dendrograms were prepared using both UPGMA and NJ algorithms. The Tarai and Bhadawari populations were close to one another and this was expected because of the contiguity of their breeding tract resulting in increased gene flow. The results of all the genetic distances were similar except ASD which is not the right method for closely related populations of a species. The inter-individual distances were also estimated and clustering of individuals was done utilizing UPGMA and NJ methods.